The correlation of self-efficacy and learning motivation with cognitive learning outcomes in high school student learning biology - Difa Arum Sari; Serafica Btari Christiyani Kusumaningrum; Shefa Dwijayanti Ramadani (Universitas Negeri Jakarta, 2026)
Learning outcomes reflect students' mastery of the material taught. However, low self-efficacy and minimal motivation to learn can be inhibiting factors in achieving optimal learning outcomes.This phenomenon was seen in some class XI MIPA students at a public school in Magelang City, who showed a lack of self-confidence when facing material that was considered difficult and appeared less involved in discussions or other class activities.Based on these conditions, this study aims to examinethe relationship between self-efficacy and learning outcomes, learning motivation and learning outcomes, and the combination of self-efficacy and learning motivation with student learning outcomes.The research approach used was quantitative with a correlational method. The population in this study were all students of grade XI MIPA, which was taken using a simple random sampling technique to obtain a sample of 101 students. Data collection was carried out using instruments in the form of questionnaires to measure self-efficacy and learning motivation, and tests to measure learning outcomes. The results of the data analysis showed that there was a significant, strong, and positive relationship between self-efficacy and learning outcomes, learning motivation and learning outcomes, and self-efficacy and learning motivation on student learning outcomes.